Earthquake source properties from analysis of dynamic ruptures and far-field seismic waves in a damage-breakage model. Issue 3 (23rd October 2020) - Kurzon, Ittai; Lyakhovsky, Vladimir; Ben-Zion, Yehuda
SUMMARY: We present results on earthquake source properties using simulations of dynamic rupture and radiated seismic waves in a continuum damage-breakage rheological model. The source properties are derived by (1) calculation of source parameters directly from the simulated ruptures and (2) observational processing of the far-field radiated waves. The seismic potency, moment, damage-related source term, rupture velocity and effective rigidity are estimated directly from the simulated sources, while the radiation pattern, dominant frequency, directivity, rupture velocity and seismic potency are calculated through analysis of the radiated waves. The potencies calculated directly from the sources are used to validate those estimated by wave analysis. The effective rigidity at the rupture zone during failure is about four times smaller than that of the intact surrounding rocks. Rupture velocity can be estimated by far-field measurements for sources with unidirectional ruptures with prominent rupture directivity. The dominant frequencies for P and S waves $f_d^S/f_d^P$ reflect clearly the rupture duration and have a ratio in the range 0.87–1.12. Seismic potencies obtained through processing the P or S waves have an overall ±15 per cent difference from the source reference values. The calculated values of the coefficient ${\rm{κ }}$, relating rupture length to corner or dominant frequency, have strong dependency on the source geometry. Using a strain-rate dependent ${\rm{κ }}$, we obtain much weaker dependencies of strain-drop on the dominant frequencies, $Δ {\rm{ε }} \propto {( {{f_d}} )^{3/4}}$, than the classical cube-dependency between stress drop and corner frequency, and corresponding weak dependency of average slip on dominant frequency, ${\rm{\bar{D}}} \propto {( {{f_d}} )^{1/2}}$ . The obtained analysis procedure and relations can be used to reduce the uncertainty of source properties derived from far-field seismic waves.